High-frequency low-loss soft magnetic material and preparation method thereof

By doping rare earth salts and adding lrO2, MoO2, CNTs, BNNT and other materials, combined with ultrasonic dispersion and secondary sintering technology, high-frequency and low-loss Mn-Zn soft ferrite materials are prepared, which solves the problem of ferrite materials at high levels. The problem of high loss at frequency significantly improves magnetic permeability and saturated magnetic induction strength and reduces eddy current loss.

CN119170402AActive Publication Date: 2024-12-20SHAANXI MASCH ACAD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411360860.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

The existing ferrite materials have high losses at high frequencies, which is difficult to meet the electronics industry's demand for high magnetic permeability and low loss.

Method used

The high-frequency and low-loss Mn-Zn soft ferrite material was prepared by doping the rare earth salt solution, and by adding lrO2, MoO2, CNTs, BNNT and other materials, combined with ultrasonic dispersion and secondary sintering technology.

Benefits of technology

It significantly improves the magnetic permeability and saturated magnetic induction strength of the material, reduces eddy current loss, improves resistivity, and improves magnetoelectric performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064903980000091
    Figure BDA0005064903980000091
  • Figure BDA0005064903980000092
    Figure BDA0005064903980000092
  • Figure BDA0005064903980000101
    Figure BDA0005064903980000101
Patent Text Reader

Abstract

The invention relates to the field of soft magnetic materials, and particularly discloses a high-frequency low-loss soft magnetic material and a preparation method thereof. The invention discloses a preparation method of a high-frequency low-loss soft magnetic material. The preparation method comprises the following steps: (1) mixing and dissolving ferric salt, zincate and manganese salt to obtain a mixed salt solution, then adding a rare earth salt solution, then adding a precipitator, stirring for reaction, and then filtering, washing, drying, calcining and refining the reacted solution to obtain rare earth doped ferrite powder; (2) performing primary sintering, crushing and screening to obtain a pre-sintered material; (3) mixing four kinds of powder of lrO2, MoO2, CNTs and BNNT to obtain intermediate powder; and (4) uniformly mixing the pre-sintered material, the intermediate powder and a lubricant, pressing to form a blank body, and carrying out secondary sintering on the blank body to obtain the Mn-Zn soft magnetic ferrite. The ferrite prepared by the preparation method disclosed by the invention has excellent magnetic performance and relatively low loss under high frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of soft magnetic materials, and more specifically, to a high-frequency low-loss soft magnetic material and a preparation method thereof. Background Art

[0002] The continuous advancement of power electronics technology has put forward higher requirements on the performance of power transmission devices. As devices continue to develop in the direction of miniaturization, integration, lightweight, and high frequency, the development of high-performance high-frequency power ferrite materials suitable for MHz level has become a core task in the field of soft magnetic material research.

[0003] Ferrite is a soft magnetic material with a spinel structure. Its high magnetic permeability, high saturation magnetization and low loss make it an indispensable component in the electronics industry. It is widely used in various fields such as communications, sensors, televisions, switching power supplies and magnetic heads. Improving the magnetic properties of ferrite and reducing its loss at high frequencies have become issues that need to be paid attention to and solved in this application field. Summary of the invention

[0004] In order to improve the magnetic properties of ferrite and reduce its loss at high frequencies, the present application provides a high-frequency, low-loss soft magnetic material and a preparation method thereof.

[0005] The present application provides a method for preparing a high-frequency, low-loss soft magnetic material using the following technical solution:

[0006] A method for preparing a high-frequency low-loss soft magnetic material, characterized in that it comprises the following steps:

[0007] (1) mixing and dissolving an iron salt, a zincate and a manganese salt to obtain a mixed salt solution, then adding a rare earth salt solution, then adding a precipitant, stirring for reaction, then filtering the solution after the reaction, washing, drying, calcining and refining the filter residue to obtain a rare earth-doped ferrite powder;

[0008] (2) sintering the rare earth-doped ferrite powder once, and then crushing and screening to obtain a pre-sintered material;

[0009] (3) mixing the four powders of lrO2, MoO2, CNTs and BNNT, adding ethanol, performing ultrasonic dispersion after magnetic stirring, filtering, washing, drying and refining the residue to obtain an intermediate powder;

[0010] (4) The pre-sintered material, intermediate powder and lubricant are mixed evenly and then pressed to form a blank, which is then subjected to secondary sintering to obtain Mn-Zn soft ferrite.

[0011] Optionally, in step (1), the molar ratio of iron salt, zinc salt and manganese salt is (2-5): (0.2-1): 1;

[0012] In step (1), the solute in the rare earth salt solution is La(NO3)3 and Pr(NO3)3 in a molar ratio of 1:(0.5-2);

[0013] In step (1), the volume ratio of the rare earth salt solution to the mixed salt solution is 1:(1-3).

[0014] Optionally, in step (2), the sintering temperature of the first sintering is 700-1000° C., and the sintering time is 1-3 h.

[0015] Optionally, in step (3), based on the pre-sintered material, the added amounts of the four powders of lrO2, MoO2, CNTs and BNNT do not exceed 0.5%-3% of the weight of the pre-sintered material.

[0016] Optionally, in step (3), the ultrasonic dispersion power is 120 W and the time is 30 min.

[0017] Optionally, in step (4), the sintering temperature of the secondary sintering is 1300-1500° C., and the sintering time is 3-7 hours.

[0018] Optionally, in step (4), the lubricant is barium stearate, and the amount of lubricant added is 0.1-1.5 wt% based on the pre-sintered material, and the pressing pressure is 10-20 T / cm 2 .

[0019] Optionally, in step (1), the refinement treatment is as follows: using acetone and polyglycol ether as grinding aids, ball milling the calcined solid at a speed of 300 r / min for 2 hours, taking it out, washing, filtering and vacuum drying to obtain rare earth-doped ferrite powder.

[0020] Optionally, in step (1), the precipitant is NH3·H2O.

[0021] In a second aspect, the present application provides a high-frequency, low-loss soft magnetic material, which is prepared using the above-mentioned preparation method.

[0022] In summary, this application has the following beneficial effects:

[0023] 1. The addition of rare earth salt solution (La(NO3)3, Pr(NO3)3) not only enhances the density of the material, but also changes the crystal structure and magnetic domain structure of the material, thereby improving its magnetic permeability, and also helps the uniform growth of grains and increases the resistivity, thereby reducing the eddy current loss of the material.

[0024] 2. By doping lrO2 and MoO2, the key properties of soft magnetic materials such as uniformity, pores and particle size are fully demonstrated, which is conducive to the growth of grains and the improvement of resistivity, thereby significantly enhancing the electromagnetic properties of the product and giving the material excellent magnetic permeability and high saturation magnetic induction intensity.

[0025] 3. CNTs and BNNTs have good electrical conductivity and magnetic properties. Their addition helps to improve the magnetic permeability of soft magnetic materials and reduce the coercive force of soft magnetic materials. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] Example

[0028] Example 1

[0029] A high-frequency, low-loss soft magnetic material, the preparation method of which is as follows:

[0030] (1) Ingredients: FeSO4, Na2Zn(OH)4, and MnSO4 are prepared in a molar ratio of 2:0.2:1, and then completely dissolved in deionized water to obtain a mixed salt solution. La(NO3)3 and Pr(NO3)3 are then prepared in a molar ratio of 1:0.5 to obtain a rare earth salt solution. The rare earth salt solution and the mixed salt solution are mixed and stirred at a volume ratio of 1:1. At this time, NH3·H2O with a volume of 2 times the volume of the solution is added, and the reaction is stirred. Then, the solution after the reaction is filtered, and the filter residue is washed with deionized water for multiple times until the pH value of the washing solution reaches about 7, and then dried in a vacuum drying oven. The dried powder is calcined at 800°C for 300 min, and then acetone and polyglycol ether are used as grinding aids. The calcined solid is ball-milled at a speed of 300 r / min for 2 h, and after being taken out, it is washed, filtered and vacuum-dried to obtain a rare earth-doped ferrite powder;

[0031] (2) Primary sintering: sintering the rare earth-doped ferrite powder at 700°C for 3 h, and then crushing and sieving the sintered material to obtain a pre-sintered material;

[0032] (3) Ultrasonic dispersion: Mix four kinds of powders, namely, lrO2, MoO2, CNTs and BNNT. Based on the pre-sintered material, the addition amounts of lrO2, MoO2, CNTs and BNNT are 0.5%, 0.5%, 0.5% and 0.5% of the weight of the pre-sintered material respectively. After mixing, add ethanol solution, turn on the magnetic stirrer, and stir the solution preliminarily to make the solution and ethanol preliminarily mixed, and then perform ultrasonic dispersion: use an ultrasonic disperser to ultrasonically treat the solution so that it is better dispersed in the ethanol solution, wherein the ultrasonic time is 30 minutes and the power is 120W. After filtering, take the filter residue and wash it with deionized water several times until the pH value of the washing solution reaches about 7, and then dry it to obtain the intermediate powder.

[0033] (4) Ball milling: The intermediate powder is mixed with the pre-sintered material, and ball milled at a speed of 300 r / min for 5 h. After being taken out, it is washed, filtered and vacuum dried to obtain a uniformly mixed powder;

[0034] (5) Compression molding: The powder obtained in (4) was mixed evenly with the lubricant barium stearate, the addition amount of barium stearate was 0.1wt%, and the temperature was 15T / cm 2 Pressed into a ring-shaped sample under pressure;

[0035] (6) Secondary sintering: The sintering was carried out in a power bell furnace atmosphere at a sintering temperature of 1300°C and kept at this temperature for 7 hours to obtain Mn-Zn soft ferrite.

[0036] Example 2

[0037] A high-frequency, low-loss soft magnetic material, the preparation method of which is as follows:

[0038] (1) Ingredients: FeSO4, Na2Zn(OH)4, and MnSO4 are prepared in a molar ratio of 4:0.6:1, and then completely dissolved in deionized water to obtain a mixed salt solution. La(NO3)3 and Pr(NO3)3 are then prepared in a molar ratio of 1:1 to obtain a rare earth salt solution. The rare earth salt solution and the mixed salt solution are mixed and stirred at a volume ratio of 1:2. At this time, NH3·H2O with a volume twice that of the solution is added, and the reaction is stirred. The solution after the reaction is then filtered, and the residue is washed with deionized water for multiple times until the pH value of the washing solution reaches about 7, and then dried in a vacuum drying oven. The dried powder is calcined at 900°C for 250 minutes, and then acetone and polyglycol ether are used as grinding aids. The calcined solid is ball-milled at a speed of 300 r / min for 2 hours, and after being taken out, it is washed, filtered, and vacuum-dried to obtain a rare earth-doped ferrite powder;

[0039] (2) Primary sintering: sintering the rare earth-doped ferrite powder at 900°C for 2 h, and then crushing and sieving the sintered material to obtain a pre-sintered material;

[0040] (3) Ultrasonic dispersion: Mix four kinds of powders, namely, lrO2, MoO2, CNTs and BNNT. Based on the pre-sintered material, the addition amounts of lrO2, MoO2, CNTs and BNNT powders are 1.5%, 1.5%, 1.5% and 1.5% of the weight of the pre-sintered material, respectively. After mixing, add ethanol solution, turn on the magnetic stirrer, and stir the solution preliminarily to make the solution and ethanol preliminarily mixed, and then perform ultrasonic dispersion: use an ultrasonic disperser to ultrasonically treat the solution so that it is better dispersed in the ethanol solution, wherein the ultrasonic time is 30 minutes and the power is 120W. After filtering, take the filter residue and wash it with deionized water several times until the pH value of the washing solution reaches about 7, and then dry it to obtain the intermediate powder.

[0041] (4) Ball milling: The intermediate powder is mixed with the pre-sintered material, and ball milled at a speed of 300 r / min for 5 h. After being taken out, it is washed, filtered and vacuum dried to obtain a uniformly mixed powder;

[0042] (5) Compression molding: The powder obtained in (4) was mixed evenly with the lubricant barium stearate, the addition amount of barium stearate was 1.0wt%, and the temperature was 15T / cm 2 Pressed into a ring-shaped sample under pressure;

[0043] (6) Secondary sintering: The sintering was carried out in a power bell furnace atmosphere at a sintering temperature of 1400°C and kept at this temperature for 5 hours to obtain Mn-Zn soft ferrite.

[0044] Example 3

[0045] A high-frequency, low-loss soft magnetic material, the preparation method of which is as follows:

[0046] (1) Ingredients: FeSO4, Na2Zn(OH)4, and MnSO4 are prepared in a molar ratio of 5:1:1, and then completely dissolved with deionized water to obtain a mixed salt solution. La(NO3)3 and Pr(NO3)3 are then prepared in a molar ratio of 1:2 to obtain a rare earth salt solution. The rare earth salt solution and the mixed salt solution are mixed and stirred at a volume ratio of 1:3. At this time, NH3·H2O with a volume twice that of the solution is added, and the reaction is stirred. The solution after the reaction is then filtered, and the filter residue is washed with deionized water for multiple times until the pH value of the washing solution reaches about 7, and then dried in a vacuum drying oven. The dried powder is calcined at 1000°C for 800 min, and then acetone and polyglycol ether are used as grinding aids. The calcined solid is ball-milled at a speed of 300 r / min for 2 h, and after being taken out, it is washed, filtered, and vacuum-dried to obtain a rare earth-doped ferrite powder;

[0047] (2) Primary sintering: sintering the rare earth-doped ferrite powder at 1000°C for 1 hour, and then crushing and sieving the sintered material to obtain a pre-sintered material;

[0048] (3) Ultrasonic dispersion: Mix four kinds of powders, namely, lrO2, MoO2, CNTs and BNNT. Based on the pre-sintered material, the addition amounts of lrO2, MoO2, CNTs and BNNT are 3.0%, 3.0%, 3.0% and 3.0% of the weight of the pre-sintered material, respectively. After mixing, add ethanol solution, turn on the magnetic stirrer, and stir the solution preliminarily to make the solution and ethanol preliminarily mixed, and then perform ultrasonic dispersion: use an ultrasonic disperser to ultrasonically treat the solution so that it is better dispersed in the ethanol solution, wherein the ultrasonic time is 30 minutes and the power is 120W. After filtering, take the filter residue and wash it with deionized water several times until the pH value of the washing solution reaches about 7, and then dry it to obtain the intermediate powder.

[0049] (4) Ball milling: The intermediate powder is mixed with the pre-sintered material, and ball milled at a speed of 300 r / min for 5 h. After being taken out, it is washed, filtered and vacuum dried to obtain a uniformly mixed powder;

[0050] (5) Compression molding: The powder obtained in (4) was mixed evenly with the lubricant barium stearate, the addition amount of barium stearate was 1.5wt%, and the temperature was 15T / cm 2 Pressed into a ring-shaped sample under pressure;

[0051] (6) Secondary sintering: The sintering was carried out in a power bell furnace atmosphere at a sintering temperature of 1500°C and kept at this temperature for 3 hours to obtain Mn-Zn soft ferrite.

[0052] Example 4

[0053] A high-frequency, low-loss soft magnetic material, the preparation method of which is as follows:

[0054] (1) Ingredients: FeSO4, Na2Zn(OH)4, and MnSO4 are prepared in a molar ratio of 2:0.5:1, and then completely dissolved in deionized water to obtain a mixed salt solution. La(NO3)3 and Pr(NO3)3 are then prepared in a molar ratio of 1:1 to obtain a rare earth salt solution. The rare earth salt solution and the mixed salt solution are mixed and stirred at a volume ratio of 1:2. At this time, NH3·H2O with a volume twice that of the solution is added, and the reaction is stirred. The solution after the reaction is then filtered, and the residue is washed with deionized water for multiple times until the pH value of the washing solution reaches about 7, and then dried in a vacuum drying oven. The dried powder is calcined at 900°C for 250 minutes, and then acetone and polyglycol ether are used as grinding aids. The calcined solid is ball-milled at a speed of 300 r / min for 2 hours, and after being taken out, it is washed, filtered, and vacuum-dried to obtain a rare earth-doped ferrite powder;

[0055] (2) Primary sintering: sintering the rare earth-doped ferrite powder at 950°C for 2 h, and then crushing and sieving the sintered material to obtain a pre-sintered material;

[0056] (3) Ultrasonic dispersion: Mix four kinds of powders, namely, lrO2, MoO2, CNTs and BNNT. Based on the pre-sintered material, the addition amounts of lrO2, MoO2, CNTs and BNNT are 3.0%, 3.0%, 3.0% and 3.0% of the weight of the pre-sintered material, respectively. After mixing, add ethanol solution, turn on the magnetic stirrer, and stir the solution preliminarily to make the solution and ethanol preliminarily mixed, and then perform ultrasonic dispersion: use an ultrasonic disperser to ultrasonically treat the solution so that it is better dispersed in the ethanol solution, wherein the ultrasonic time is 30 minutes and the power is 120W. After filtering, take the filter residue and wash it with deionized water several times until the pH value of the washing solution reaches about 7, and then dry it to obtain the intermediate powder.

[0057] (4) Ball milling: The intermediate powder is mixed with the pre-sintered material, and ball milled at a speed of 300 r / min for 5 h. After being taken out, it is washed, filtered and vacuum dried to obtain a uniformly mixed powder;

[0058] (5) Compression molding: The powder obtained in (4) was mixed evenly with the lubricant barium stearate, the addition amount of barium stearate was 1.5wt%, and the temperature was 15T / cm 2 Pressed into a ring-shaped sample under pressure;

[0059] (6) Secondary sintering: Sintering was performed in a power bell furnace atmosphere at a sintering temperature of 1340°C for 5.5 h to obtain Mn-Zn soft ferrite.

[0060] Comparative Example

[0061] Comparative Example 1

[0062] A high-frequency, low-loss soft magnetic material, the preparation method of which is different from that of Example 4 in that the amounts of raw materials used are different, as shown in Table 1.

[0063] Comparative Example 2

[0064] A high-frequency, low-loss soft magnetic material, the preparation method of which is different from that of Example 4 in that the amounts of raw materials used are different, as shown in Table 1.

[0065] Comparative Example 3

[0066] A high-frequency, low-loss soft magnetic material, the preparation method of which is different from that of Example 4 in that the amounts of raw materials used are different, as shown in Table 1.

[0067] Comparative Example 4

[0068] A high-frequency, low-loss soft magnetic material, the preparation method of which is different from that of Example 4 in that the amounts of raw materials used are different, as shown in Table 1.

[0069] Comparative Example 5

[0070] A high-frequency, low-loss soft magnetic material, the preparation method of which is different from that of Example 4 in that the amounts of raw materials used are different, as shown in Table 1.

[0071] Comparative Example 6

[0072] A high-frequency, low-loss soft magnetic material, the preparation method of which is different from that of Example 4 in that the amounts of raw materials used are different, as shown in Table 1.

[0073] Table 1 The amount of each raw material in the examples and comparative examples

[0074]

[0075] Performance testing

[0076] The above embodiments and comparative examples were tested for magnetic permeability, magnetic induction intensity, eddy current loss, and operating frequency resistivity. The test results are shown in Table 2:

[0077] Table 2 Magnetic properties test of embodiments and comparative examples

[0078]

[0079]

[0080] It can be seen from Table 2 that the addition of lrO2, MoO2, CNTs, and BNNT is beneficial to improving the magnetic induction intensity and resistivity, and to a certain extent improves the eddy current loss of the material. Within the specified range, the more the added content, the more conducive it is to improving the magnetic properties.

[0081] From the comparison between Example 4 and Comparative Examples 1-4, it can be seen that when the four additives of lrO2, MoO2, CNTs and BNNT are added at the same time, the initial magnetic permeability, magnetic induction intensity and resistivity of the material are all improved, while the eddy current loss is reduced. This shows that the four additives have a significant synergistic effect in improving the magnetic properties of Mn-Zn ferrite materials.

[0082] In Comparative Examples 1-4, although each additive added alone or in combination can improve the performance to a certain extent, the effect is not as significant as when the four additives are added simultaneously, which further proves the importance of the synergistic effect of the four additives.

[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a high-frequency, low-loss soft magnetic material, characterized in that: The following steps are involved: (1) mixing and dissolving an iron salt, a zincate and a manganese salt to obtain a mixed salt solution, then adding a rare earth salt solution, then adding a precipitant, stirring for reaction, then filtering the solution after the reaction, washing, drying, calcining and refining the filter residue to obtain a rare earth-doped ferrite powder; (2) sintering the rare earth-doped ferrite powder once, and then crushing and screening to obtain a pre-sintered material; (3) mixing the four powders of lrO2, MoO2, CNTs and BNNT, adding ethanol, performing ultrasonic dispersion after magnetic stirring, filtering, washing, drying and refining the residue to obtain an intermediate powder; (4) The pre-sintered material, intermediate powder and lubricant are mixed evenly and then pressed to form a blank, which is then subjected to secondary sintering to obtain Mn-Zn soft ferrite.

2. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (1), the molar ratio of iron salt, zinc salt and manganese salt is (2-5): (0.2-1): 1; In step (1), the solute in the rare earth salt solution is La(NO3)3 and Pr(NO3)3 in a molar ratio of 1:(0.5-2); In step (1), the volume ratio of the rare earth salt solution to the mixed salt solution is 1:(1-3).

3. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (2), the sintering temperature of the first sintering is 700-1000° C., and the sintering time is 1-3 hours.

4. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (3), based on the pre-sintered material, the added amount of the four powders of lrO2, MoO2, CNTs and BNNT does not exceed 0.5%-3% of the weight of the pre-sintered material.

5. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (3), the power of ultrasonic dispersion is 120 W and the time is 30 min.

6. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (4), the sintering temperature of the secondary sintering is 1300-1500° C., and the sintering time is 3-7 hours.

7. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (4), the lubricant is barium stearate, and the amount of lubricant added is 0.1-1.5 wt% based on the pre-sintered material, and the pressing pressure is 10-20 T / cm 2 .

8. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (1), the refinement treatment is as follows: using acetone and polyglycol ether as grinding aids, ball milling the calcined solid at a speed of 300 r / min for 2 hours, taking it out, washing, filtering and vacuum drying to obtain rare earth doped ferrite powder.

9. The method for preparing a high-frequency low-loss soft magnetic material according to claim 1, characterized in that: In step (1), the precipitant is NH3·H2O.

10. A high-frequency, low-loss soft magnetic material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electrochromic display device and method for manufacturing an electrochromic display device

    CN103323998A

  • Fabrication method of Fe-based amorphous soft magnetic composite powder core

    CN106373694A

  • Iron-based nanocrystalline magnetic core and preparation method thereof

    CN115472414A

  • Manganese-zinc power ferrite material, preparation method thereof and switching power supply transformer

    CN115724656A

  • Surface treatment metallic material having excellent electromagnetic wave absorptivity, its manufacturing method, and case for electronic device using metallic material

    JP2007287846A